Pain and Opioid Consumption and Mobilization after Surgery: Post Hoc Analysis of Two Randomized Trials. (January 2022) - Rivas, Eva; Cohen, Barak; Pu, Xuan; Xiang, Li; Saasouh, Wael; Mao, Guangmei; Minko, Paul; Mosteller, Lauretta; Volio, Andrew; Maheshwari, Kamal; Sessler, Daniel I.; Turan, Alparslan
Abstract : Background: Early mobilization is incorporated into many enhanced recovery pathways. Inadequate analgesia or excessive opioids may restrict postoperative mobilization. The authors tested the hypotheses that in adults recovering from abdominal surgery, postoperative pain and opioid consumption are inversely related to postoperative mobilization, and that postoperative mobilization is associated with fewer potentially related complications. Methods: The authors conducted a subanalysis of two trials that enrolled adults recovering from abdominal surgery. Posture and movement were continuously monitored for 48 postoperative hours using noninvasive untethered monitors. Mobilization was defined as the fraction of monitored time spent sitting or standing. Results: A total of 673 patients spent a median [interquartile range] of 7% [3 to 13%] of monitored time sitting or standing. Mobilization time was 1.9 [1.0 to 3.6] h/day for patients with average pain scores 3 or lower, but only 1.2 [0.5 to 2.6] h/day in those with average scores 6 or greater. Each unit increase in average pain score was associated with a decrease in mobilization time of 0.12 (97.5% CI, 0.02 to 0.24; P = 0.009) h/day. In contrast, there was no association between postoperative opioid consumption and mobilization time. The incidence of the composite of postoperative complications was 6.0% (10 of 168) in the lower mobilization quartile, 4.2% (7 of 168) in the second quartile, and 0% among 337 patients in the highest two quartiles ( P = 0.009). Conclusions: Patients recovering from abdominal surgery spent only 7% of their time mobilized, which is considerably less than recommended. Lower pain scores are associated with increased mobility, independently of opioid consumption. Complications were more common in patients who mobilized poorly. Abstract : The authors combined data from two abdominal surgery trials and evaluated pain, opioid use, and mobilization. Pain was associated with less mobilization, but opioid consumption was not. Overall mobilization was low, and complications were more frequent in those who mobilized poorly.